Seminal Attributes, Freezability and their Interrelationships in Zebu Cattle and Buffalo Bulls from Central Gujarat - Pathak, PK; Dhami, AJ; Chaudhari, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was carried out on nine healthy mature breeding bulls (3 each of Gir, Surti and Murrah breed) to evaluate their fresh and frozen semen quality and their interrelationships. The ejaculates immediately after collection were evaluated for routine physicomorphological attributes, including HOS test. The ejaculates (n=72) having >75% initial motility were diluted @ 80 millionsperm/ml using TFYG extender and the French mini straws filled were frozen in liquid nitrogen vapour using a programmablebiofreezer. Thawing of straws was done at 37°C for 30 sec and assessed for freezability by conventional technique. All the cattleand buffalo bulls donated consistently normal thick creamy yellow and thick milky white semen, respectively. In Gir, Suti and Murrahbulls (n=24 ejaculate each) the seminal attributes such as ejaculate volume (6.69±0.17, 3.12±0.10 and 3.96±0.16 ml,p
Keywords: Gir; Surti; Murrah; Seminal attributes; Freezability; Interrelationships